Perempuan, Pil KB, dan Batu Empedu: Hubungan Durasi Kontrasepsi dengan Risiko Cholelithiasis - Kwando, Feliciana; Setyawan, Yuswanto (Universitas Nahdlatul Ulama Blitar, 2025)
The use of oral contraceptive pills (OCPs) is widely recognized as an effective method of birth control among women of reproductive age. However, prolonged exposure to synthetic estrogen and progesterone may pose a risk for gallstone formation (cholelithiasis). This study aimed to investigate the association between the duration of OCP use and the incidence of cholelithiasis in reproductive-age women. Employing a quantitative cross-sectional approach, 100 purposively selected female respondents aged 20–45 years were assessed through structured questionnaires, interviews, and confirmed ultrasonography (USG) results. Statistical analyses using Chi-Square and Spearman’s rank correlation revealed a significant relationship between longer duration of pill use and increased risk of gallstone formation (p < 0.05). These findings underscore the hepatobiliary impact of long-term hormonal contraceptive use, even in asymptomatic users. The novelty of this research lies in highlighting duration as a predictive factor, which has not been emphasized in current family planning policies. This study recommends integrating risk-based contraceptive counseling and early detection protocols into primary health care services, particularly for long-term users. Further longitudinal studies are necessary to confirm causal relationships and expand the applicability of these findings.